Influence of PEG 4000 concentration dissolution rate of ketoprofen in solid dispersion system of ketoprofen-PEG 4000 - Fikri Alatas; Sundani Nurono S.; Sukmadjaja Asyarie (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Influence of PEG 4000 concentration dissolution rate of ketoprofen was studied in solid dispersion system of ketoprofen-PEG 4000. Solid dispersion system was prepared by melting method with various weight ratio of ketoprofen-PEG 4000, i.e. 2:1, 1:1, 1:3, and 1:4. The dissolution test was carried out using the paddle method at temperature of 37±0,5°C and 50 rotations per minute (rpm) in 900 mL of hydrochloric acid buffer solution at pH 1.2. The dissolution rate of ketoprofen improved by increasing PEG 4000 concentration. Incorporation of sodium lauryl sulfate into solid dispersion system of ketoprofen-PEG 4000 enhanced the dissolution rate of ketoprofen.Key words : solid dispersion, ketoprofen, PEG 4000, sodium lauryl sulfate